2019
DOI: 10.1016/j.bpj.2018.11.2843
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Exocytotic Arrest by the Complexin C-Terminus

Abstract: Hindering premature vesicular fusion is key to build up a molecularly primed ready releasable pool. Complexin-II (CpxII), a 16 KD cytosolic protein, inhibits non-synchronous vesicle fusion at release sites, and by that accumulates a ready releasable pool of primed vesicles that are released in synchrony upon immediate elevation of intracellular calcium. Functionally, CpxII is equipped with four independent yet synergetic domains. A central helix mediates the CpxII-SNARE (Nethylmaleimide-sensitive factor (NSF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Neurotransmitter or hormone release requires a basal membrane fusion machinery, and one or more Ca 2+ -sensors to link fusion to the electrical activity of the cell. The machinery driving vesicleto-membrane fusion consists of the SNAREs (Fang and Lindau, 2014;Jahn and Fasshauer, 2012), associated proteins Munc18 and Munc13 necessary for SNARE-complex assembly (Rizo and Xu, 2015), and Ca 2+ -sensors of the synaptotagmin (Syt) family (Pinheiro et al, 2016) together with complexins (Makke et al, 2018;Trimbuch and Rosenmund, 2016). Syts harbor two C2-domains, which can bind to Ca 2+ and phospholipids (in 8 of the 17 Syt isoforms present in the mammalian genome), and to SNAREs (Sudhof, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotransmitter or hormone release requires a basal membrane fusion machinery, and one or more Ca 2+ -sensors to link fusion to the electrical activity of the cell. The machinery driving vesicleto-membrane fusion consists of the SNAREs (Fang and Lindau, 2014;Jahn and Fasshauer, 2012), associated proteins Munc18 and Munc13 necessary for SNARE-complex assembly (Rizo and Xu, 2015), and Ca 2+ -sensors of the synaptotagmin (Syt) family (Pinheiro et al, 2016) together with complexins (Makke et al, 2018;Trimbuch and Rosenmund, 2016). Syts harbor two C2-domains, which can bind to Ca 2+ and phospholipids (in 8 of the 17 Syt isoforms present in the mammalian genome), and to SNAREs (Sudhof, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…5). The Cpx C-terminus competes with SNAP25-SN1 for binding to the SNARE complex and thereby halts progressive SNARE complex formation before the triggering 31 . Our study revealed that the rescue of the function of full-length Cpx requires a high concentration of CpxI CTD, and abundant CTD peptide is able to enhance the inhibitory function of CpxI 31 .…”
Section: Resultsmentioning
confidence: 99%